Pharmacokinetics of H002, a novel S1PR1 modulator, and its metabolites in rat blood using liquid chromatography-tandem mass spectrometry - Jiaqi Mi; Manman Zhao; Shu Yang; Shuang Yang; Jing Jin; Xiaojian Wang; Qiong Xiao; Jinping Hu; Yan Li (Elsevier, 2016)
A rapid and sensitive liquid chromatography-tandem mass spectrometry (LC-MS/MS) method was developed and validated for the simultaneous determination of H002 and its phosphorylated metabolite, H002-P and hydroxylated metabolite H002-M, in rat blood. H001, an analogue of H002, was used as the internal standard. Blood samples were prepared by simple protein precipitation. The analytes and internal standard were separated on a Zorbax SB-C18 column with a gradient mobile phase consisting of methanol and water containing 0.1% formic acid at a flow rate of 0.2 mL/min with an operating temperature of 20 °C. The detection was performed on a triple quadrupole tandem mass spectrometer with positive electrospray ionization in multiple-reaction monitoring mode. Linear detection responses were obtained from 0.2-100 ng/mL for H002 and H002-M, while 0.5-100 ng/mL for H002-P. The intra- and inter-day precision (RSD%) was within 11.76%, with the accuracy (RE%) ranging from -9.84% to 9.12%. The analytes were shown to be stable during sample storage, preparation and analytic procedures. The method was applied to determine the pharmacokinetics of H002 in rats, and a preliminary study showed that the pharmacokinetics of H002 correlated with its biological effect on peripheral blood lymphocytes.